A produção textual no processo de aprendizagem da língua escrita: Práticas docentes em uma turma de Alfabetização - Santos, Lainy Martinelli dos (2020)
The present work aimed to understand the ways in which children, in the process of Literacy, are given the opportunity to produce texts, even without having learned the entire alphabetic linguistic code. This is a study that was carried out in a public el